PENGARUH EDTA DALAM PENENTUAN KANDUNGAN TIMBAL DAN TEMBAGA PADA KERANG HIJAU (Mytilus viridis) - Suaniti, Ni Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 2 No 1)
Effect of addition Etylene Diamines Tetra Acetate (EDTA) on plumbum (Pb) and cuprum (Cu) contents in green mussel (Mytilus viridis) has been decreased their metal content . One part of sample was destructed with ten part of acid mixture. Using a mixture 10 mL sulphuric acid and 40 mL nitric acid conc. After destruction the sample was analysed using Atomic Absorption Spectrometry (AAS) with calibration curve method. Result showed that Pb contents found in dry green mussel was between 28.6128 - 29.8442 mg/kg and Cu contents found in dry green mssel was between 2.4239 – 2.8858 mg/kg. After adding EDTA 0,1 M at pH 4 for 30 minute the contents of Pb and Cu decreased. The content of Pb in dry sample decreased to 27.3829 - 27.9988 mg/kg, while the content of Cu in in dry sample decreased to 0.2579 – 0.6919 mg/kg
Keywords: plumbum, Cuprum, green mussel (Mytilus viridis), sulphuric acid, nitric acid conc., EDTA, Atomic Absorption Spectrometry